Industrial usage of hydrogen in Europe - Mičieta, Jakub; Vlčková, Jana; Bič, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Hydrogen shows great potential as a sustainable energy source for the industrial sector, particularly in steel, ammonia, methanol, and oil production. Using hydrogen can lessen reliance on fossil fuel, increase energy efficiency and lower greenhouse gas emissions. The EU is supporting the development of a hydrogen economy through projects like fit-for-55 package, RepowerEU or even green deal. There are also numerous initiatives such as the Clean Hydrogen Partnership, the European Clean Hydrogen Alliance and others. However, challenges remain, including high cost of hydrogen, lack of infrastructure and limited supply. The main goal of the thesis is to assess the viability of steel production using hydrogen in Europe. Utilization of hydrogen in steel industry has potential the potential to decrease the world’s CO2 emissions by 7-9%. However, for hydrogen further in this industry it is essential to resolve all the obstacles standing in its way- high hydrogen prices, insufficient logistics or lack of renewable energy sources for green hydrogen production. Despite the difficulties, hydrogen as an industrial energy source for either steel production or in general has significant potential advantages.
Vedoucí práce: Jana Vlčková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses